THE EFFECT OF EXPLICIT, IMPLICIT INSTRUCTIONS AND LEARNING STYLES ON STUDENTS’ SENTENCE STRUCTURE ACHIEVEMENT - Marisi Debora (BAHAS, 2011)
The objectives of this study are to investigate whether Explicit Instruction and Implicit Instructions techniques significantly affect the students’ sentence structure achievement, to find out whether the students’ learning styles affect students’ sentence structure achievement and to find out whether there is an interaction between explicit and Implicit instructions and learning styles to students’ sentence structure achievement. An experimental research with factorial design 2x2 was used in this research. There were 120 students from 2008 Academic year of English Department State University of Medan taken as sample of this research. The post test was given to both groups. The data were analyzed by applying Two-Way ANOVA. The result of testing the first hypothesis showed that that explicit and Implicit instructions significantly affect students’ sentence structure achievement. The result of the testing the second hypothesis showed that students’ learning style do not significantly affect students’ sentence structure achievement. The result of the testing the third hypothesis showed that there is interaction between instructions techniques and learning styles on students’ sentence structure achievement. After the Scheffe test was applied, it showed that students who have Field Independent learning style got higher result if they were taught by Explicit instruction and students who have Field Dependent learning style got higher result if they were taught by Implicit instruction. Key Words: explicit instruction; implicit instruction; learning styles